FOCUS GROUP DISCUSSION UNTUK MEMBANGUN MODEL KEGIATAN TANGGUNG JAWAB SOSIAL LINGKUNGAN - Roostika, Ratna; Susilowati, Christin; Muafi, ' (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
The implementation of Corporate Social Responsibility (CSR) by corporations operating in Indonesia has nowadays becoming an obligator y. CSR has been defined as activities representing compan y’s corporate social responsibility and environment. Both private and public companies should allocate their budget to CSR activities. When implementing different kinds of CSR programs, many companies have encountered problems concerning what kinds of program that match with the needs of the societies and environment surround the company’s location. In particular, there have been questions about finding the kind of CSR programs that match with compan y’s vision -mission as well as strategic directions. This community service program was conducted to assist the company in building a CSR model specific to company characteristics as well as finding priority identifications program relating to company’s CSR (social and environment responsibility). The program is conducted in one of Government (BUMN) company in the food sector. The method practiced for this community service is socialization on CSR program, Focus Group Discussion (FGD) and questionnaire distribution for building CSR model and CSR program identifications. Finding have identified some main areas of priority program such as: education and training, health improvement, infrastructure and facility upgrading, supporting worship facilities, technology assistance, building human resource talents, managing natural environment and minimizing potential risk of natural disaster.